Pengembangan E-Modul Berbasis Problem Based Learning menggunakan Kvisoft Flipbook Maker - Mumpuni, Ragil Sri; Hartatiana, Hartatiana; Wardani, Ambarsari Kusuma (Edumatica : Jurnal Pendidikan Matematika, 2023)
In the independent curriculum, the integration of technology into learning should be optimized, the use of technology in learning, one of which is the usage of e-modules. This research aims to produce e-modules using the kvisoft flipbook maker application based on Problem Based Learning that are valid and practical and effective on student learning outcomes. The type of research used is development research using the Analysis, Design, Development, Implementation and Evaluation (ADDIE). The research subjects were class VII students at SMP Negeri 4 Palembang. The data collection techniques used were questionnaires, interviews and tests. Validity data was obtained from validation of numeracy literacy with 3 validators and practicality data was obtained from the practicality questionnaire given to students. Meanwhile, the potential effect is seen based on student grades. The research results show an average validity of 3.76 in the valid category, practicality of 3.93 in the very practical category, and student test results that have a potential effect on good learning outcomes. So it can be concluded that the e-module using the kvisoft flipbook maker application based on Problem Based Learning for class VII has been proven to be valid and practical and effective on student learning outcomes.